My life with the Eskimo - Stefansson, Vilhjalmur, 1879-1962.; Anderson, Rudolph Martin, 1876-1961. (New York, Macmillan Company, 1913)
"Report on the natural history collections of the expedition, by Rudolph Martin Anderson, PH. D.": p. 436-527. Mode of access: Internet.